in Quantitative Aptitude retagged by
336 views
1 vote
1 vote

Let $x$ and $y$ be positive real numbers such that $\log _{5}(x+y)+\log _{5}(x-y)=3$, and $\log _{2}y-\log _{2}x=1-\log_{2}3$. Then $xy$ equals

  1. $250$
  2. $25$
  3. $100$
  4. $150$
in Quantitative Aptitude retagged by
13.4k points
336 views

1 Answer

1 vote
1 vote
Given that,

$ \log_{5} (x+y) + \log_{5} (x-y) = 3 $

$ \Rightarrow \log_{5} (x+y)(x-y) = 3  \quad \left[\because \log_{a} m + \log_{a} n = \log_{a}(mn)\right]$

$ \Rightarrow \log_{5} (x^{2}-y^{2}) = 3 $

$ \Rightarrow (x^{2}-y^{2}) = 5^{3} \quad [\because \log_{a}b = x \Rightarrow b = a^{x}]$

$ \Rightarrow (x^{2}-y^{2}) = 125 \quad \longrightarrow (1) $

And, $\log_{2}y – \log_{2}x = 1 - \log_{2}3 $

$ \Rightarrow \log_{2} \left( \frac{y}{x} \right) = 1 – \log_{2}3 \quad \left[\because \log_{a} m – \log_{a} n = \log_{a} \left(\frac{m}{n} \right) \right] $

$ \Rightarrow \log_{2} \left( \frac{y}{x} \right) + \log_{2}3 = 1 $

$ \Rightarrow \log_{2} \left( \frac{3y}{x} \right) = 1 $

$ \Rightarrow \frac{3y}{x} =2^{1} $

$ \Rightarrow 2x = 3y $

$ \Rightarrow x = \frac {3y}{2} \quad \longrightarrow (2) $

Put the value of $x$ in the equation $(1),$ we get

$ x^{2} – y^{2} = 125 $

$ \Rightarrow \left(\frac{3y}{2} \right)^{2} – y^{2} = 125 $

$ \Rightarrow \frac{9y^{2}}{4} – y^{2} = 125 $

$ \Rightarrow 9y^{2} – 4y^{2} = 500  $

$ \Rightarrow 5y^{2} = 500 $

$ \Rightarrow y^{2} = 100 $

$ \Rightarrow y = 10 $

From equation $(2),$ we get

$ x = \frac{3y}{2} = \frac {3 \times 10}{2} = 15 $

$\therefore$ The value of $xy = 15 \times10 = 150 $

Correct Answer $: \text{D}$
edited by
10.3k points
Answer:

Related questions

Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true